Spatial reorganisation of the somatosensory cortex in a patient with a low-grade glioma. Issue 5 (5th May 2019) - Das, Sunit; Morrison, Melanie; Tam, Fred; Graham, Simon
Abstract : Multiple authors have speculated that functional plasticity of the neural networks required for speech and motor function may occur in the setting of low-grade brain tumours. Here, we present the case of a 39-year-old right-handed woman found on presentation for intermittent right-hand tingling and twitching to have a low-grade glioma involving the somatosensory cortex on both structural and functional MRI. Intraoperative awake mapping identified gyral dissociation of the somateosensory areas for right arm and leg sensation. These findings demonstrate that brain plasticity may be dramatic in the setting of a low-grade glioma, and emphasise the critical need for careful brain mapping when considering tumour resection in these patients.